Leverage Influence on Accounting Policy Choices and Reporting Behavior (gjstudies, 2017)
This research investigates the underexplored nexus between corporate financial leverageand the strategic selection of accounting policies, positing that leverage acts not merely asa financial metric but as a primary institutional force shaping reporting behavior. Movingbeyond traditional agency and contracting cost frameworks, we introduce a novel ’LeverageInduced Reporting Pressure’ (LIRP) model that conceptualizes debt covenants and creditorscrutiny as creating a distinct reporting environment characterized by asymmetric information pressures and outcome-dependent validation. The study employs a mixed-methodologyapproach, combining a longitudinal analysis of accounting policy changes in highly leveraged firms from 1995 to 2004 with a series of experimental simulations involving financialexecutives. Our findings reveal a non-linear relationship between leverage levels and accounting conservatism, with a critical threshold beyond which firms exhibit a pronounced shifttowards income-increasing and asset-valuing policies, contrary to the conservative bias predicted by debt covenant hypotheses. We identify a unique ’reporting elasticity’ phenomenon,where the sensitivity of accounting choices to earnings targets intensifies disproportionatelywith leverage. Furthermore, the research documents the emergence of ’covenant-proximatereporting’, a strategic clustering of aggressive accounting estimates in periods immediatelypreceding debt covenant tests. These results contribute a new theoretical lens for understanding financial reporting, suggesting that high leverage environments foster a calculativeculture where accounting policy becomes a direct tool for managing creditor perceptions andcovenant compliance, with significant implications for standard setters, auditors, and creditanalysts concerned with the quality and sustainability of reported earnings in debt-heavycapital structures.